Detection of Tannery Effluents Induced DNA Damage in Mung Bean by Use of Random Amplified Polymorphic DNA Markers. (10th March 2014) - Raj, Abhay; Kumar, Sharad; Haq, Izharul; Kumar, Mahadeo
Abstract : Common effluent treatment plant (CETP) is employed for treatment of tannery effluent. However, the performance of CETP for reducing the genotoxic substances from the raw effluent is not known. In this study, phytotoxic and genotoxic effects of tannery effluents were investigated in mung bean ( Vigna radiata (L.) Wilczek). For this purpose, untreated and treated tannery effluents were collected from CETP Unnao (UP), India. Seeds of mung bean were grown in soil irrigated with various concentrations of tannery effluents (0, 25, 50, 75, and 100%) for 15 days. Inhibition of seed germination was 90% by 25% untreated effluent and 75% treated effluent, compared to the control. Plant growth was inhibited by 51% and 41% when irrigated with untreated and treated effluents at 25% concentration. RAPD technique was used to evaluate the genotoxic effect of tannery effluents (untreated and treated) irrigation on the mung bean. The RAPD profiles obtained showed that both untreated and treated were having genotoxic effects on mung bean plants. This was discernible with appearance/disappearance of bands in the treatments compared with control plants. A total of 87 RAPD bands were obtained using eight primers and 42 (48%) of these showed polymorphism. Irrigating plants with untreated effluent caused 12 new bands to appear and 18 to disappear. Treated effluent caused 8 new bands and the loss of 15 bands. The genetic distances shown on the dendrogram revealed that control plants and those irrigated with treated effluent were clustered in one group (joined at distance of 0.28), whereas those irrigated with untreated effluent were separated in another cluster at larger distance (joined at distance of 0.42). This indicates that treated effluent is less genotoxic than the untreated. Nei's genetic similarity indices calculated between the treatments and the control plants showed that the control and the plants irrigated with treated tannery effluent had a similarity index of 0.75, the control and plants irrigated with untreated 0.65, and between the treatments 0.68. We conclude that both untreated and treated effluents contain genotoxic substances that caused DNA damage to mung beans. CETP Unnao removes some, but not all, genotoxic substances from tannery effluent. Consequently, use of both untreated and treated wastewater for irrigation poses health hazard to human and the environment.